2020
DOI: 10.1530/ec-19-0499
|View full text |Cite
|
Sign up to set email alerts
|

Personality types in individuals with type 1 and type 2 diabetes

Abstract: Objective The Type A personality, characterized by impatience, strong career ambition and competitiveness, is associated with greater sensitivity to external stress. Type 1 diabetes (T1D) is an auto-immune disease, which is potentially influenced by stress, unlike type 2 diabetes (T2D). The aim of this study was to assess whether individuals with T1D and T2D exhibited significant differences on the Type A personality scale. We also assessed personality in patients with thyroid auto-immune diseases to validate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…In the 70s and 80s Type A personality typology was at the center of studies on the link between personality and cardiovascular diseases [ 13 , 14 ]. Over the years, several studies have confirmed an association between the Type A personality and worse health conditions, particularly cardiovascular diseases and diabetes [ 15 19 ]. However, many other studies have obtained contrasting results [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the 70s and 80s Type A personality typology was at the center of studies on the link between personality and cardiovascular diseases [ 13 , 14 ]. Over the years, several studies have confirmed an association between the Type A personality and worse health conditions, particularly cardiovascular diseases and diabetes [ 15 19 ]. However, many other studies have obtained contrasting results [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It also does not agree with Rouland et al study, which found that Type A Bortner scores were significantly higher in T1D patients than in T2D patients. 8 Smoking was found not to be correlated to type A behavior pattern. This result is consistent with Hughes et al study, which found that Type A and Type B smokers do not differ in smoking behavior or tobacco and nicotine intake.…”
Section: Discussionmentioning
confidence: 82%
“…The personality of patients with type 2 diabetes is characterized by neuroticism and psychoticism and shows a negative correlation with extraversion (33), and diabetes type 1 is characterized by internalized anger that generates excessive competitiveness colored with aggression, perfectionism. (17) Following the processing of the results, the patients with diabetes, in terms of personality, presented significantly higher results from a statistical point of view to neuroticism / anxiety and activity than the control group. The high level of anxiety and neuroticism were also highlighted in other studies (8,9,33) but the need for high activity of patients with diabetes was outlined only in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Studies in the field (14,17) describe differently the personality of patients with type 1 and type 2 diabetes. The personality of patients with type 2 diabetes is characterized by neuroticism and psychoticism and shows a negative correlation with extraversion (33), and diabetes type 1 is characterized by internalized anger that generates excessive competitiveness colored with aggression, perfectionism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation